The Degree of Effectiveness of Education Bridges Program in Teaching Science at primary stage in Ajloun Directorate from Teacher Perspective - Ayub, Soua'd Yousef Hamed (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the degree of effectiveness of education bridges program in teaching science at primary stage in Ajloun directorate from teacher perspective , the researcher used the Descriptive approaches, study Sample consisted from (160) Female and male of science teacher, chosen randomly, to collect data Questioner used, which consisted (24) paragraph, divided to two sector (Technical field, interact with the program), the result of SPSS analysis shown that the degree of the degree of effectiveness of education bridges program in teaching science at primary stage in Ajloun directorate from teacher perspective was High with average (3.76 out of 5) , The finding also showed there is no statistically significant differences at (α=0.05) refers to teacher sex (male and female) in addition there were statistically significant differences refers to teacher qualification in favor of (High education).